A high resolution capacitive sensing system for the measurement of water content in crude oil - Zubair, M. (MDPI AG, 2014)
This paper presents the design of a non-intrusive system to measure ultra-low water content in crude oil. The system is based on a capacitance to phase angle conversion method. Water content is measured with a capacitance sensor comprising two semi-cylindrical electrodes mounted on the outer side of a glass tube. The presence of water induces a capacitance change that in turn converts into a phase angle, with respect to a main oscillator. A differential sensing technique is adopted not only to ensure high immunity against temperature variation and background noise, but also to eliminate phase jitter and amplitude variation of the main oscillator that could destabilize the output. The complete capacitive sensing system was implemented in hardware and experiment results using crude oil samples demonstrated that a resolution of Â±50 ppm of water content in crude oil was achieved by the proposed design. Â© 2014 by the authors; licensee MDPI, Basel, Switzerland.